Synthesis of Cyclodextrin Inclusion Complexes with (h-Cyclopentadienyl)iron Derivatives as Potential Nonlinear Optics Materials* - Dias, A. R. (2012)
Dicarbonyl(h-cyclopentadienyl)iron tetrafluoroborates containing aromatic nitriles as ligands were synthesized. These and other (h-cyclopentadienyl)iron derivatives were used to obtain intercalation compounds with b-cyclodextrin.